A Novel Type of Ureteral Stents in the Treatment of a Bilateral Iatrogenic Transaction of the Ureters. (29th July 2013) - Mazza, Ernesto; Mondaini, Francesco; Abdulcadir, Dalmar; Raspanti, Claudio; Citone, Michele; Lapini, Alberto
Abstract : This report illustrates the case of a patient who suffered an iatrogenic complete injury of both ureters after a complex surgical procedure to remove a large sacral chordoma. Ureteral recanalization was achieved with two removable, autoexpandable, and polytetrafluoroethylene covered nitinol stents. To our knowledge, we describe the first application of this type of stents to treat a bilateral ureteral transection. Despite the bad general conditions of the patient, the ureteral stents successfully restored and maintained the bilateral ureteral continuity.